Gas Chromatography-Mass Spectrometer Electron Ionization (GC-MS -EI)method for the Analysis of MalathionResidue in Tomato (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
In this a study tomato sampleswere collected from Khartoum, extracted with acetone, dichloromethane and petroleum ether (1:1:1) and cleaned up by florisil column. Malathion quantitative determination is carried out by gas chromatograph-mass spectrometerusing the optimum ionization mode electron ionization (EI). The detection ofmalathionis confirmed by retention time and comparison of primary and secondary ions.Recovery studies   were performed at two spikes (0.5,0.25mg kg-1) fortification levels of malathion and the recovery obtained ranged from 81% to 97%. The method showed good linearity(R²> 0.995) over the range assayed (from 0.05 to 7.0mg L-1) and the calculated limits of detection (LOD) and quantification(LOQ) were0.03 mg kg-1and 0.11 mg kg-1, respectively. These limits  werelower than the maximum residue levels(MRL) established by European legislations (0.5mg kg-1).